APLIKASI KONSEP PEMIKIRAN KAORU ISHIKAWA MELALUI DIAGRAM FISHBONE DALAM MENINGKATKAN MUTU SISWA - Mochammad Safrotulloh; Septi Gumiandri (LPPM Bunga Bangsa Cirebon, 2020)
Education is a system which contains aspects of vision, mission, goals, curriculum, teaching materials, teachers, students, management, infrastructure, costs, environment and so on. The goal is the direction achieved or aimed by education. Likewise, the provision of education cannot be separated from a goal which should be achieved. This is evidenced by the provision of education experienced by the Indonesian nation. This study aims to describe the method of the principal of Madrasah Diniyah Takmiliyah Awaliyah (MDTA) in solving students’ moral problems which arise in Madrasah environment using the Fishbone diagram. This study uses qualitative methods which aims to understand all the problems that occur in the field. The data sources of this research are the principal, teaching staff and the community. The form of this research is the students’ moral problems that arise in Madrasah Diniyah Takmiliyah Awaliyah (MDTA). The importance of collecting data; such as observation, interviews and documentation in a study is as a tool to strengthen the results of research validity. The results of this study indicate that the principal in solving students’ moral problems at MDTA Al-Hidayah is by conducting periodic evaluations of students. The evaluation is through meetings between teachers which are held every month, and every three months a meeting held with parents and society. However, the students' bad behavior is caused by uncontrolled association either by parents, teachers or society. The solution is cooperations between teachers, parents and community should be active. It is to always monitor the students. So that, moral damage to the nation's generation does not occur.